Financial globalization as positive integration: monetary technocrats and the Eurodollar market in the 1970s. Issue 4 (4th July 2021) - Braun, Benjamin; Krampf, Arie; Murau, Steffen
Abstract: International political economy (IPE) has explained financial globalization as the result of states deciding to open up and liberalize domestic financial systems. Complementing this 'negative integration' view, we present a theory of financial globalization during the 1970s that emphasizes the importance of 'positive integration.' Credit money systems are characterized by public-private infrastructural entanglements, the management of which require substantial institutional work by monetary technocrats, both at the domestic and at the international level. To illustrate our theory, we trace the expansion of the Eurodollar market during the 1970s. Drawing on archival records from the 'Standing Committee on the Euro-currency Market' at the Bank for International Settlements, we show how this group of G-10 central bankers sought to elevate the management of infrastructural entanglements from the domestic to the international level. By ensuring that the Eurodollar market did not interfere with domestic monetary governability, while seeking to provide protection for issuers of Eurodollars, monetary technocrats helped establish the institutional infrastructure for the expansion and globalization of the offshore US dollar system.